Prevalence and factors associated with carrying out prenatal tests in the COVID-19 pandemic: A cross-sectional study. - Fabri, Eduarda Rockenbach; Canônico, Simone Biff; da Silva, Rosane Meire Munhak; Ferreira, Helder; Zilly, Adriana; Contiero, Ana Paula (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2023)
Objective: To identify the prevalence of prenatal screening and its associated factors during the COVID-19 pandemic in a Brazilian health region. Method: A cross-sectional and descriptive research study, carried out with 408 puerperal women in the maternity hospitals from the 9th Health Region, through survey and consultation of the pregnant women’s medical records and cards. The Chi-square test was used, assuming a significance level of p<0.05. Results: There was low prevalence of prenatal exams: 67% in the first trimester, 59.2% in the second and 48.98% in the third. Non-white race and prenatal care initiation after the 14th week are associated with low performance of serological/biochemical tests. Conclusion and implications for the practice: The performance of prenatal tests was not satisfactory during the pandemic period, allowing us to verify the existence of gaps in prenatal care quality. In adverse situations, as was the case in the COVID-19 pandemic, nurses can use strategies that guarantee prenatal care continuity and comprehensiveness, especially among the most vulnerable populations.